Effect of Profitability, Sales Growth, Leverage, Cash Flow Ratio, and Managerial Ownership On Financial Distress - Arafah, Febriana; Kusumawati, Eny (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Financial distress is a condition where the company cannot or has difficulty fulfilling its obligations to creditors. This study aims to analyze the effect of profitability, sales growth, leverage, cash flow ratio and managerial ownership on financial distress in non-financial companies on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used in this study was purposive sampling. A total of 411 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results provide empirical evidence that profitability, leverage, and cash flow ratios affect financial distress. Meanwhile, sales growth and managerial ownership have no effect on financial distress.